Combining Mentoring Programs with Cash Transfers for Adolescent Girls in Liberia : Baseline Report - Hallman, Kelly; Kelvin, Elizabeth; Ozler, Berk; Seban, Juliette; Kuhlik, Erica; Alton, Cooper; Kamara, Joseph; Goodman, Sarah (World Bank, Washington, DC, 2016)
This report presents findings from the baseline assessment of International Rescue Committee's (IRC) Girl Empower (GE) program in Nimba County, Liberia. GE seeks to help 13 to 14 year-old girls make healthy life choices and decrease their risk of sexual abuse. The program centers on weekly meetings between girls and trained local mentors, during which the girls learn about life skills and financial literacy. GE also holds monthly discussion groups for participants' caregivers, and trains local health and psychosocial care providers on how to improve and expand services for survivors of gender-based violence. This baseline report is part of a cluster-randomized controlled trial, which aims to assess the program's impact 24 months after baseline. 21 percent of the baseline sample of 13-14 year-old females reported having previously had sex. Within this group, 29 percent indicated that their first sexual act was non-consensual. Among all GE girls, 37 percent reported having experienced sexual violence of some type, such as being physically forced to have sex, non-physically pressured (coerced/persuaded) to have sex, someone unsuccessfully attempting to have sex with them, and being touched in a sexual way. The levels of nonconsensual first sex and any experience of nonconsensual sex are at the high end of the range reported by the UNICEF Violence against Children Surveys (VACS) in Swaziland, Tanzania, Kenya and Zimbabwe. As the VACS reporting is for (a variety of) age ranges, each of which is higher than that in this study, the levels of sexual violence reported here are very high in comparison.